To Research the Effects of Storage Time on Autotransfusion based on Erythrocyte Oxygen-Carrying Capacity and Oxidative Damage Characteristics. (17th May 2021) - Li, Zhen-Zhou; Jia, Dong-Lin; Wang, Huan; Zhou, Xiao-Fang; Cheng, Yong; Duan, Li-Shuang; Yin, Lei; Wei, Han-Wei; Guo, Wei; Guo, Jian-Rong
Autotransfusion refers to a blood transfusion method in which the blood or blood components of the patient are collected under certain conditions, returned to himself when the patient needs surgery or emergency after a series of storing and processing. Although autotransfusion can avoid blood-borne diseases and adverse reactions related to allogeneic blood transfusion, a series of structural and functional changes of erythrocytes will occur during extension of storage time, thus affecting the efficacy of clinical blood transfusion. Our research was aimed to explore the change of erythrocyte oxygen-carrying capacity in different storage time, such as effective oxygen uptake (Q), P50, 2, 3-DPG, Na + -K + -ATPase, to detect membrane potential, the change of Ca 2+, and reactive oxygen species (ROS) change of erythrocytes. At the same time, Western blot was used to detect the expression of Mitofusin 1 (Mfn1) and Mitofusin 2 (Mfn2) proteins on the cytomembrane, from the perspective of oxidative stress to explore the function change of erythrocytes after different storage time. This study is expected to provide experimental data for further clarifying the functional status of erythrocytes with different preservation time in patients with autotransfusion, achieving accurate infusion of erythrocytes and improving the therapeutic effect of autologous blood transfusion, which has important clinical application value.